SKILLS THAT CONTRIBUTE TO EFFECTIVE MANAGEMENT OF META-COMPETENCIES (Scientific journal of the Fergana State University, 2026)
In this article, Metacompetence refers to a person's ability to manage their knowledge and skills, apply them effectively, and develop them, representing a set of knowledge and skills in this area. This concept mainly covers the pedagogical processes of education and areas of personal development. The first and most important quality of metacompetence is self-awareness. A person can effectively plan their personal development by identifying their strengths and weaknesses, as well as interests and goals. Through this quality, people gain a better understanding of themselves and their future successes and achievements are highlighted.